Association of Physical Activity With Bioactive Lipids and Cardiovascular Events. Issue 4 (19th July 2022) - Hoshi, Rosangela A.; Liu, Yanyan; Luttmann-Gibson, Heike; Tiwari, Saumya; Giulianini, Franco; Andres, Allen M.; Watrous, Jeramie D.; Cook, Nancy R.; Costenbader, Karen H.; Okereke, Olivia I.; Ridker, Paul M; Manson, JoAnn E.; et al.
Abstract : Background: To clarify the mechanisms underlying physical activity (PA)-related cardioprotection, we examined the association of PA with plasma bioactive lipids (BALs) and cardiovascular disease (CVD) events. We additionally performed genome-wide associations. Methods: PA-bioactive lipid associations were examined in VITAL (VITamin D and OmegA-3 TriaL)-clinical translational science center (REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01169259; N=1032) and validated in JUPITER (Justification for the Use of statins in Prevention: an Intervention Trial Evaluating Rosuvastatin)-NC (REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00239681; N=589), using linear models adjusted for age, sex, race, low-density lipoprotein-cholesterol, total-C, and smoking. Significant BALs were carried over to examine associations with incident CVD in 2 nested CVD case-control studies: VITAL-CVD (741 case-control pairs) and JUPITER-CVD (415 case-control pairs; validation). Results: We detected 145 PA-bioactive lipid validated associations (false discovery rate <0.1). Annotations were found for 6 of these BALs: 12, 13-diHOME, 9, 10-diHOME, lysoPC(15:0), oxymorphone-3b-D-glucuronide, cortisone, and oleoyl-glycerol. Genetic analysis within JUPITER-NC showed associations of 32 PA-related BALs with 22 single-nucleotide polymorphisms. From PA-related BALs, 12 are associated with CVD. Conclusions: We identified a PA-related bioactive lipidome profile out of which 12 BALs also had opposite associations with incident CVD events.